2020
DOI: 10.1038/s41598-019-57157-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of human skeletal muscle cells with inhibitors of diacylglycerol acyltransferases 1 and 2 to explore isozyme-specific roles on lipid metabolism

Abstract: Diacylglycerol acyltransferases (DGAT) 1 and 2 catalyse the final step in triacylglycerol (TAG) synthesis, the esterification of fatty acyl-CoA to diacylglycerol. Despite catalysing the same reaction and being present in the same cell types, they exhibit different functions on lipid metabolism in various tissues. Yet, their roles in skeletal muscle remain poorly defined. In this study, we investigated how selective inhibitors of DGAT1 and DGAT2 affected lipid metabolism in human primary skeletal muscle cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…It has been previously suggested that FFAs may affect lipid metabolism in differentiated human myotubes [ 14 , 15 ]. In human myoblasts, C18[2]c exclusively led to lipid accumulation within 48 h. Although the long-term effects of C18[2]c were not studied here, we assume that unceasing lipid accumulation may affect signaling pathways and gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously suggested that FFAs may affect lipid metabolism in differentiated human myotubes [ 14 , 15 ]. In human myoblasts, C18[2]c exclusively led to lipid accumulation within 48 h. Although the long-term effects of C18[2]c were not studied here, we assume that unceasing lipid accumulation may affect signaling pathways and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Immortalized rodent muscle cell lines have been employed to study the molecular mechanisms of FFA actions in the regulation of metabolism, apoptosis and insulin resistance [ 9 , 10 , 11 , 12 ]. To extend the relevance of the outcomes to humans, some studies have utilized in vitro differentiated human myotubes to study the effects of FFAs on lipid metabolism, mitochondrial function and the expression of particular genes of interest [ 13 , 14 , 15 , 16 ]. In organisms, FFAs commonly exhibit diverse primary or secondary structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGAT1 and DGAT2 are enzymes that catalyze the final step of TAG synthesis. Our recent study has shown that acute inhibition of DGAT1 and DGAT2 using selective enzymatic inhibitors had distinct effects on lipid metabolism in myotubes (127). Inhibition of DGAT1, the most abundant isoform in skeletal muscle, resulted in an almost totally abolished incorporation of exogenous FAs into TAG and LDs.…”
Section: Effects Of Exercise and Possible Pharmacological Targets For...mentioning
confidence: 99%
“…DGAT1 and DGAT2 are key enzymes important for the final step in LD formation. DGAT1 inhibition is known to inhibit LD formation thus leading to a reduction in the number of LDs in cells, but some studies have shown that DGAT2 inhibition can lead to a paradoxical increase of LDs 40 42 . Therefore, we hypothesized that DGAT2 inhibition could increase both LD size and number, leading to both recruitment of APOL1 G2/G2 and improved cell survival.…”
Section: Resultsmentioning
confidence: 98%